Analisis Resepsi Audiens Gen Z Terhadap Peran Domestik di Serial Bridgerton - Audrey Nadya Adhavati Azzahra; Anter Venus (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study examines female Gen Z audiences' reception in Indonesia of women's domestic roles in Bridgerton, highlighting gender inequalities like marriage pressure and gender discrimination, relevant to patriarchal culture in Indonesia today. The aim is to explore Gen Z's perceptions of roles as wife, mother, and daughter, using Stuart Hall's reception theory, with a focus on the rarely discussed role of daughter. Using descriptive qualitative methods, semi-structured interviews were conducted with ten informants aged 21-27 in Jabodetabek, selected for demographic variations. Results show interpretations through preferred reading (full acceptance), negotiated reading (equality negotiation), and oppositional reading (stereotype rejection). Key findings include criticism of marital financial transparency, positive views of mothers as advisors, and negotiation of eldest daughters' role model duties. The novelty lies in demonstrating how active audiences reinterpret media messages influenced by personal experiences, expanding Gen Z studies on gender shifts in Indonesia’s patriarchy, and emphasizing the role of daughters. Practically, it urges the media to create inclusive content, challenging stereotypes, and promoting equality.